Ligand conjugated liposomal drug delivery system for enhanced brain uptake of ampicillin - Lala, R.; Nandvikar, N.; Agnihotri, S. (Creative Pharma Assent, 2016)
Targeting of antimicrobial agents by means of liposomes may be of great value in the treatment of intra or extracellular infections compare to conventional forms of antimicrobial therapy. In the present study Ampicillin loaded non-targeted Polyethylene glycolated liposomes and targeted Glutathione Polyethylene glycollated liposomes of about 132.14 nm size were prepared with 80 % of drug entrapment. Prepared liposomes were evaluated for in vitro, in vivo release profile and brain uptake studies. Results of these studies revealed more absorption of drug than standard Ampicillin solution and non targeted liposomes (Auc0-6h 1858.908 µg h/ml) and 3.5 times increase in brain uptake. Incorporation of polyethylene glycol in the liposomes increased the drug concentration and circulation time in plasma as well as in the extracellular fluid of brain thus improved therapeutic availability of Ampicillin trihydrate.